Conhecimento popular sobre plantas do cerrado como subsídio para propostas de educação ambiental - Borges, Magno Rodrigues (2009)
Ethnobotany and Environmental Education assignments have the interdisciplinary in common and can be supplementary. While the Ethnobotanic worries, for instance, with the vision and the knowledge about native Cerrado plants, working with its basis on botanic and in the anthropology, the Environmental Education worries about arranging the values and necessary knowledge to the sustainability of a population. The research has had as its aim to evaluate through some ethnobotany methodologies, the knowledge of native vegetal species and their uses in the urban area of Martinésia (Uberlândia MG) and develop, through the Intervention-Research, future Environmental Education projects in a more social-interactionist view to the referred environment conservation. In order to reach this goal interviews were made with the community to identify partnerships that could advertise their knowledge on Cerrado plants (Key Informants) as well as partnerships which had the capacity of intervening in the popular and scientific knowledge and finally organize Environmental Education practices (Multipliers). Ethnobotanic methodologies were adopted (Interviews, walk-in-thewoods, and boards) with the Key Informers in order to check out their popular knowledge, while the Multipliers passed through interviews and helped in the Environmental Education workshop. 49 species of useful plants were identified through the ethnobotanic method walk-in-the-woods , being the most frequent uses the medicinal (45%) and the nourishing (28%). Within the native medicinal plants use, 57% from the highlighted procedures were the ones through tea, the leaf was the most used part from the plant (33%) and the prescriptions from the most treated illnesses per such plants were to the breathing system (20%), genitor (18%), digestive (17%),and in the skin (14%). The boards utility in the interviews weren t enough to the Key Informers to talk about their knowledge, its application in the workshops presented an efficient result. The interviews (with the community, the Key Informers and the Multipliers) highlighted the community physical knowledge (social aspects, economics, biodiversity and others) as well as the symbolic (values). The Environmental Education should base in several factors from this community like: the social-economical, to a better selection from the target group; the educational in order to have a close approach to the community language and to contrast the formal and informal education; moreover the cultural aspects that permeate this population environment and knowledge. The local culture might also be respected, in which can have rational elements or not, due to two reasons: in order not to people feel hurt according to their ideologies and in order to have a continuity in the discussions about the environment as a whole (from the natural to the human aspects) to the social-environmental sustainability.